Point-of-use water treatment improves recovery rates among children with severe acute malnutrition in Pakistan: results from a site-randomized trial. Issue 16 (22nd August 2018) - Doocy, Shannon; Tappis, Hannah; Villeminot, Nicolas; Suk, Ann; Kumar, Deepak; Fazal, Shahid; Grant, Angeline; Pietzsch, Silke
Abstract: Objective: To evaluate effectiveness of point-of-use water treatment in improving treatment of children affected by severe acute malnutrition (SAM). Design: Programme sites were randomized to one of four intervention arms: (i) standard SAM treatment; (ii) SAM treatment plus flocculent/disinfectant water treatment; (iii) SAM treatment plus chlorine disinfectant; or (iv) SAM treatment plus ceramic water filter. Outcome measures were calculated based on participant status upon exit or after 120d of enrolment, whichever came first. Child anthropometric data were collected during weekly monitoring at programme sites. Child caregivers were interviewed at enrolment and exit. Use of water treatment products was assessed in a home visit 4–6 weeks after enrolment. Setting: Dadu District, Sindh Province, Pakistan. Subjects: Children ( n 901) aged 6–59 months with SAM and no medical complications. Results: Recovery rates were 16·7–22·2 % higher among children receiving water treatment compared with the control group. The adjusted odds of recovery were approximately twice as high for those receiving water treatment compared with controls. Mean length of stay until recovery was 73 (sd 24·6) d and mean rate of weight gain was 4·7 (sd 3·0) g/kg per d. Differences in recovery rate, length of stay and rate of weight gain between intervention groups were not statistically significant. Conclusions: Incorporating point-of-use water treatment into outpatient treatment programmes for children with SAM increased nutritional recovery rates. No significant differences in recovery rates were observed between the different intervention groups, indicating that different water treatment approaches were equally effective in improving recovery.